Inteligencia emocional en universitarios homosexuales, víctimas de discriminación (2022)
The present study aims to get insight into the emotional intelligence state of homosexual university students who are victims of discrimination, taking into consideration the themes of emotions, Goleman's emotional intelligence, sexual orientation and discrimination against homosexuality, from a cognitive-behavioral theoretical perspective. Data was collected through a non- experimental quantitative research approach. The participants of the study were 5 self-identified homosexuals, who reported having experienced discrimination because of their sexual orientation and who are currently enrolled in their university studies. The results show that the participants display a high level of empathy and also indicate lack of self- awareness, self-regulation, motivation and social skills on these 5 study subjects.